A novel approach to fault detection for fuzzy stochastic systems with nonhomogeneous processes - Yin, Y.; Shi, Peng; Liu, F.; Teo, Kok Lay; Teo, Kok Lay (Elsevier Inc, 2015)
In this paper, we consider a class of fuzzy stochastic systems with nonhomogeneous jump processes. Our focus is on the design of a fuzzy fault detection filter that is sensitive to faults but robust against unknown inputs. Furthermore, the error filtering system is stochastically stable. With reference to an H1 performance index and a new performance index, sufficient conditions to ensure the existence of a fuzzy robust fault detection filter are derived. Simulation studies are carried out, showing that the proposed fuzzy robust FD filter can rapidly detect the faults correctly.